Development of biocentric-network structure of vinnytsia environmental network using geoinformational technologies - Крижановський, Євгеній Миколайович; Нагорна, Анастасія Володимирівна (Eastern-European Journal of Enterprise Technologies, 2014)
Approach to developing a generalized scheme of the Vinnytsia city ecological network, which, unlike the existing one provides a connectivity evaluation of the biocentric - network structure of the developed ecological network scheme that allows to quantify the quality of the proposed ecological network has got further development. The main structural elements of Vinnytsia city ecological network project were determined. According to the research tasks: - the development of a general algorithm of the city ecological scheme, which details the design process and the connectivity evaluation of the ecological network was performed; - the method of analysis of the connectivity evaluation of the biocentric - network structure of the developed ecological network scheme was proposed; - the approbation of the developed algorithm and the proposed evaluation method on the example of the Vinnytsia city ecological network was carried out. A project of the generalized Vinnytsia city ecological network scheme using geoinformation package "Panorama" was developed. The developed ecological network project was presented at a meeting with Mayor of Vinnytsia at the participation of heads of departments and offices of the City Council. For the specification, implementation and effective use of the developed project of the generalized ecological network scheme, it is necessary: 1) to improve and detail the general schemes of the Vinnytsia city ecological network; 2) to agree the project with the corresponding government authorities; 3) to develop recommendations for the proper functioning of the city ecological network. Specified and detailed city ecological network can be used when developing management decisions on saving biodiversity and protection of the city environment.